Hydride Reduction by a Sodium Hydride–Iodide Composite. Issue 11 (16th February 2016) - Too, Pei Chui; Chan, Guo Hao; Tnay, Ya Lin; Hirao, Hajime; Chiba, Shunsuke
Abstract: Sodium hydride (NaH) is widely used as a Brønsted base in chemical synthesis and reacts with various Brønsted acids, whereas it rarely behaves as a reducing reagent through delivery of the hydride to polar π electrophiles. This study presents a series of reduction reactions of nitriles, amides, and imines as enabled by NaH in the presence of LiI or NaI. This remarkably simple protocol endows NaH with unprecedented and unique hydride‐donor chemical reactivity. Abstract : A new job for an old friend : Sodium hydride (NaH) is widely used as a Brønsted base in chemical synthesis and reacts with various Brønsted acids, but it rarely behaves as a reducing reagent through delivery of the hydride to polar π electrophiles. It has now been found that nitriles, amides, and imines undergo reduction by NaH as a hydride donor in the presence of LiI or NaI (see scheme).